Determinants of Work‐at‐Home Arrangements for German Employees. (19th August 2015) - Sarbu, Miruna
Abstract: Flexible work arrangements such as allowing employees to work at home are increasingly widespread among firms. Using individual‐level data from 10, 884 German employees, this paper analyses the determinants of working at home. The analysis is based on descriptive analyses and a discrete choice model. The results reveal that men have a higher probability to work at home, but women are more likely to work at home intensively. Education, tenure, and the use of computers increase the probability of working at home whereas firm size and young age of employees reduce it. Having children less than 6 years old, overtime, and work time have a positive impact on both working at home and on working at home intensively.